50 Years after Kiel '69. Teaching Geography and Geography Education in Times of Change - Haversath, Johann-Bernhard (Journal of Geography Education, 2020)
Young scientists demanded in 1969 to give up Regional Geography, the previous paradigm. This meant a new chapter for Geography Education and Teaching Geography: curricula had to be changed, textbooks with new objectives were generated, role plays and programmed instructions completed the work in class. From a social perspective change was overdue. Comparative international research shows that the impulse of the Kiel conference was successful – with restrictions. At present, all achievements will be on trial again and be proven towards other competing disciplines. In principle, Geography will certainly be able to keep up with "mega topics" such as climate change, migration and many more. Whether it will prevail politically, however, may be a different issue.
Keywords: Geography Education, history of Geography, changing paradigms, textbooks, basic concepts